"Don't forget to be awesome" : the role of social learning as a component of belonging in virtual communities: a case study of the Youtube fan community "Nerdfighteria" - Steenkamp, Elri Colleen (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2018)
The growth of the Internet has allowed fans who consume various media products, to interact and convene with other who share similar interests in online fan communities. Historically the study of fans has focused on pleasure and enjoyment as the main motivating factors why individual fans join, stay and participate in fan communities. This study, however, suggests that learning as a component of belonging has been underestimated within contemporary fan studies. Close examination of the literature of fan studies and the social practices of online fan communities reveal that these spaces may serve as fertile spaces for learning and the sharing of knowledge. Daily learning occurs within multiple spheres, including personal interests, peer culture, and academic content; all elements which can be found within fan communities. This study used the social learning theory "communities of practice" (CoP) model developed by Wenger (1998) to understand of this element of learning and knowledge sharing that seems to take places within fan communities. This study explores learning as a component of belonging to online fan communities by using the fan community of the YouTube personalities Vlogbrothers, which has named itself Nerdfighteria, as a case study. Through a qualitative research approach, which includes participation observation methods and qualitative interviews, this thesis has analysed the fan community Nerdfighteria, and used two Nerdfighter fan Facebook groups, the global NERDFIGHTEIRIA and local Nerdfighters South Africa, as case studies to evaluate whether the elements of learning taking place within these spaces serves as a motivating factor for belonging and participation. The results of this research support the idea that learning plays a role within the fan community Nerdfighteria and thus that it functions as a CoP. Fans within the global NERDFIGHTERIA Facebook group use this fan space to discuss and debate content related to their media of choice; thereby learning and acquiring knowledge as a CoP. The Nerdfighters South Africa Facebook group, despite the learning potential, fails to function as a CoP because it is no longer functionally allows for shared learning. Online fan communities, this research found, have the potential to serve as functioning communities of practice (CoP) only if they embody the characteristics and practicalities consistent with a learning space. Overall these fan groups may be categorised as communities of interests but sub-sections within these communities fit the criteria of a community of practice due to the kind of learning that is taking place. This research supports an alternative, yet promising, approach to the study of fan online communities which prioritises learning.
Keywords: Nerdfighteria (Online); Social learning; Online social networks; Belonging (Social psychology); Communities of practice; YouTube (Firm)